Post‐Operative 'Post‐isms': Details of the 21st‐Century Educations of Architecturalists. (28th June 2021) - Garcia, Mark
Abstract: The teaching of History and Theory can be as speculative as a design studio, giving the subject a projective emphasis. Mark Garcia, Senior Lecturer at the University of Greenwich, London, renamed the related course at the university as Histories/Theories/Futures and redesigned its content. The programme operates in a much more propositional way than it previously did and often constitutes the intellectual armature of the Masters student's design projects. He describes his modus operandi and shows some of his students' work.